(untitled) (INCH : Journal of Infant and Child Healthcare, 2023)
The impact of diarrhea in toddlers besides death is dehydration, growth retardation (failure to thrive), malnutrition and a negative impact on children’s cognitive development. The aim of the study is the relationship between MP-ASI sanitation hygiene and maternal personal hygiene with the incidence of diarrhea in toddlers in the working area of the Harapan Raya Public Health Center. This type of research is a descriptive study with a cross sectional approach. The population in the study were toddlers aged 6-24 months in the working area of the Harapan Raya Public Health Center. Sampling by purposive sampling as many as 48 people. The statistical test uses Chi Square analysis with a 95% degree of confidence. The statistical test results showed that there was a relationship between maternal personal hygiene and the incidence of diarrhea in toddlers (p = 0.030) and there was no relationship between MP-ASI sanitation hygiene and the incidence of diarrhea (p = 0.252). The conclusion of this study is that the indication of the occurrence of diarrhea is 65%, while the indicator of not having diarrhea in children is 35%. It is recommended for puskesmas to further activate counseling related to risk factors for diarrheal disease in toddlers.